Successful Collaborative Governance Building Permanent Residence Post-Natural Disaster in Palu City - Hasbullah Hasbullah (UIN Sunan Gunung Djati, 2024)
This study analyses the success of Collaborative Governance in the Construction of Phase I Permanent Residential in the Tondo sub-district after the Earthquake, Tsunami, and Liquefaction on September 28 2018, in Palu City. This research used qualitative methods by collecting data through observation, interviews, and documentation. Data analysis was carried out in the stages of data collection, condensation, display, and conclusion. The theory applied was the Collaborative Governance Model from 1) Face-to-face dialogue, 2) Trust Building, 3) Commitment to process, 4) shared understanding, and 5) Intermediate Outcomes.Â The result showed that from the theoretical aspect, the triumph achieved in collaborative governance of permanent housing was because, since the beginning of the direct conversation, an agreement on the division of authority had been reached, wherein the Provincial Nasional Disaster Management Agency (NDMA) prepared the land for the project, the Palu City NDMA was responsible for providing the infrastructure, and the Tzu Chi Buddhist Foundation has the competence to build the constant home. The accomplishment of establishing this initial covenant was followed up well, along with the consistency toward trust building, commitment to the process, and shared understanding to attain good intermediate outcomes.